Characteristic of endocrine cells of rat small intestine after administration of cryopreserved placenta on the background of acute aseptic peritoneal inflammation. - Shepitko, K. V. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Modern conceptions about mechanisms of inflammation of the small intestine could not be formed without an understanding of intercellular relationships that are realized by biologically active signaling molecules produced by endocrine cells. Methods. The experimental study has been carried out on the small intestine extracted from 140 adult male rats. Electron and light microscopy methods were used. Acute aseptic inflammation was modeled by intraperitoneal carrageenan injection; influence of subcutaneously cryopreserved placenta injection was analyzed. Results. After modeling of the acute aseptic peritoneal inflammation the maximal increase of ECL-cells was noted on the 21st day. The slowest restoration of endocrine cells number occurred on all measured parameters and was observed on day 30th of the observation. In case of administration of cryopreserved placenta at the early stages (days 3rd – 7th) the increase of average number of EC- and ECL-cells promoted the enhanced permeability of vessels in the lamina propria. The decrease in number of P-cells prevented the development of hyperacid gastritis. Reduction in the average number of D1- cells prevented the excessive vasodilatation and facilitated the excretion of excess fluid from the foci of inflammation. In simultaneous subcutaneous administration of cryopreserved placenta and modeling of acute aseptic peritoneal inflammation the number of ЕС- and ЕСL-cells increased, accelerating the vascular response to inflammation. Conclusion. Active appearance of low-differentiated cells including those with “shapes of mitosis” on the day 14th indicates restoration of structural components of the small intestine mucosa and processes of absorption and parietal digestion after placenta administration during acute aseptic inflammation.